Antibacterial Effects of Moringa oleifera Leaf Extract Against Enterococcus faecalis in vitro - Piasti Sopandani; Bernard Ongki Iskandar; Taufiq Ariwibowo; Melanie Sadono Djamil (Faculty of Dentistry, Universitas Trisakti, 2020)
Background: The aim of endodontic treatment is to eliminate bacteria from the root canal. Bacterial removal from the root canal can be achieved with a mechanical approach using an instrument and a disinfecting irrigation agent. Enterococcus faecalis is the most prevalent bacteria found in root canals. Research studies have also been conducted to examine irrigation systems using herbal products such as drumstick tree leaf (Moringa oleifera) instead of NaOCl. Active compounds in M. oleifera, such as flavonoids, tannins, saponins, alkaloids, phenolics, and triterpenoids, possess antibacterial effects. Objectives: The aim of this study is to assess the antibacterial effect of drumstick tree extract (M. oleifera) in several concentrations (25%, 50%, 75%, and 100%) as an irrigation solution against E. faecalis through in the root canal ex vivo. Methods: This study used 24 mandibular premolars, divided into six category groups. Group 1 received 5.25% NaOCl as a positive control, Group 2 received 25% M. oleifera extract, Group 3 received 50% M. oleifera extract, Group 4 received 75% M. oleifera extract, Group 5 received 100% M. oleifera extract, and Group 6 received irrigation using phosphate‑buffered saline as a negative control. Quantitative polymerase chain reaction methods used to analyze the E. faecalis number in the root canal after treatment with M. oleifera extract. Results: A one‑way ANOVA showed significant differences (P = 0.05) between the three types of irrigation solutions against E. faecalis. Among the six study groups, the most prominent efficacy was found in Groups 1, 4, and 5. Conclusion: M. oleifera extract solution at concentrations of 75% and 100% is as effective as 5.25% NaOCl. This extract may be used as an alternative irrigation agent for root canal treatment. However, further studies are warranted to examine the toxicity effect.